1992
DOI: 10.1159/000182316
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations in Plasma ACTH, Cortisol and Beta-Endorphin Levels in Cocaine Addicts

Abstract: In order to establish possible alterations in the hypothalamic pituitary-adrenal axis and in ACTH-related opioids in cocaine addicts, plasma ACTH, cortisol and β-endorphin levels were measured throughout the day in 9 cocaine addicts [age: 27 ± 5 years (mean ± SE); weight: 72 ± 6.1 kg, duration of cocaine addiction: at least 2 years] on the day of their admission to a recovery community for drug abusers (first test) and after 15 days of abstinence (second test). Nine normal controls (age: 28 + 6 years; weight: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…This enhanced response of the HPA axis during withdrawal from chronic cocaine has been reported 24 h to 48 h after the last cocaine injection in rats (Peltier et al, 2001;Zhou et al, 2003). Similar results have been reported in human cocaine addicts (Vescovi et al, 1992;Mendelson et al, 1998).…”
Section: Introductionsupporting
confidence: 82%
“…This enhanced response of the HPA axis during withdrawal from chronic cocaine has been reported 24 h to 48 h after the last cocaine injection in rats (Peltier et al, 2001;Zhou et al, 2003). Similar results have been reported in human cocaine addicts (Vescovi et al, 1992;Mendelson et al, 1998).…”
Section: Introductionsupporting
confidence: 82%
“…Consistent with this possibility, we observed a significant inverse correlation between basal CORT levels and the magnitude of the CORT response from baseline. Notably, it does not appear that human cocaine addicts experience similar reductions in HPA function, since basal cortisol and/or ACTH levels are reportedly unchanged (Mendelson et al, 1988) or elevated (Vescovi et al, 1992;Buydens-Branchey et al, 2002;Contoreggi et al, 2003) during withdrawal. This disparity between our preclinical findings and the clinical data suggests that either there are subtle differences in the effects of cocaine SA on the HPA axis between rats and humans or that our protocol does not precisely simulate the human condition, thus highlighting that, although the long-access SA approach may be useful for investigating certain aspects of cocaine addiction, it is by no means a complete model.…”
Section: Basal Cort Levelsmentioning
confidence: 99%
“…With repeated cocaine administration, adaptive changes in the HPA axis emerge and can be observed as disrupted basal HPA function during drug withdrawal in cocaine-dependent individuals (Vescovi et al, 1992;Buydens-Branchey et al, 2002;Contoreggi et al, 2003) and in rats (Sarnyai et al, 1998;Zorilla et al, 2001;Zhou et al, 2003). Less is known about how the response of the HPA axis to stressors is altered as a consequence of prior cocaine use.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a single dose of cocaine or of stress on ACTH secretion, however, are significantly lower in cocaine-dependent men than in occasional cocaine users or normal subjects (Mendelson et al, 1998;Brady et al, 2009;Back et al, 2010), showing tolerance as found in the animal model after chronic cocaine administration (Zhou et al, 1996). Higher basal plasma ACTH and cortisol levels have been reported in cocaine addicts 1 day after the cessation of cocaine self-administration (Vescovi et al, 1992). In cocaine addicts with depressive symptoms, basal plasma cortisol levels are increased during early cocaine abstinence (Elman et al, 1999;Buydens-Branchey et al, 2002), an effect that may persist weeks and even months during abstinence (Contoreggi et al, 2003;Wilkins et al, 2005).…”
Section: Introductionmentioning
confidence: 99%